Perceived benefits and perceived risks effect on online shopping behavior with the mediating role of consumer purchase intention in Pakistan - Bhatti, Anam; Rehman, Shafique ur (Universiti Utara Malaysia, 2019)
The purpose of this study is to examine the relationship between different factors including perceived benefits, perceived risks and online shopping behavior with the mediating role of consumer purchase intention. Online shopping states the recent trends of being able to purchase anything from home with a single click. The main focus of this study is to check the influence of four major variables: convenience, product variety, product risk, and privacy risk which were derived from related literature. Data were collected from 380 students from different universities using simple random sampling. PLS-SEM was used in this study and the results showed that benefits had a positive influence and that risk had a negative influence on online shopping behavior.